Reflection of the audit of contracts according to "related services" on the report of the auditor: applied research in Palestine International Hotel Company / shareholding company (Journal of Accounting and Financial Studies ( JAFS ), 2020)
The issue of auditing contracts according to the related services is one of the important topics It has also become necessary to develop traditional procedures and auditing according to international standards to improve the profession of accounting and auditing. From this standpoint, the research aims to indicate the reflection of the contracting audit in accordance with the related services on the auditor's report. in line with the new directions regarding the need to adopt international standards in the Iraqi environment as the research problem focused on the non-comprehensiveness of the audit programs that deal with auditing contracts according to assurance commitments to contribute obtaining Governing evidence, The research was based on the hypothesis that the adoption of International Auditing Standard 4400 to audit contracts in the hotel industry positively affects the report of the auditor. The researchers reached a set of conclusions and recommendations, Among the most prominent conclusions are the existence of compatibility and harmony between the international auditing standard 4400 "related services" and contracting activity in the hotel industry, by providing detailed instructions for setting and applying the audit programs according to agreed procedures. The study concluded with many recommendations, the most important of which is the need to take advantage of the guidance provided by the international auditing standard 4400 in the contracting activity in the hotel industry to develop and implement audit programs in accordance with agreed procedures.